Dimensional Accuracy Study of Open Cellular Structure CoCrMo Alloy Fabricated by Selective Laser Melting Process - Zahrul Adnan, Mat Taib; W. S., Wan Harun; S. A., Che Ghani; M. F. F., Ab Rashid; Mohd Asnawi, Omar; Hazlen, Ramli (Trans Tech Publications, Switzerland, 2016)
Designing orthodontic implants with desired physical and biological performance and to fabricate net shape with complex anatomical shapes is still a challenge. Cautious design approaches followed by systematic manufactural techniques that can achieve balanced physical performance in mono block implants mechanics is necessary to accomplish this objective. Metal additive manufacturing (MAM) technique such as selective laser melting (SLM) process is progressively being utilized for new biomaterials such as cobalt-chrome-molybdenum (CoCrMo). This study was designed to determine a dimensional accuracy of open cellular structures CoCrMo samples with designed volume based porosity ranging between 0% (full dense) to 80%. A maximum 2.10% shrinkage was obtained by 80% designed porosity sample. Samples with higher volume-to-surface area (full dense) demonstrated low total amount of shrinkage as compared to lower volume-to-surface area (80% designed porosity)